2005
DOI: 10.1096/fj.05-4313fje
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium‐derived factor (PEDF) is an endogenous antiinflammatory factor

Abstract: Pigment epithelium-derived factor (PEDF) is a potent angiogenic inhibitor. Reduced PEDF levels are associated with diabetic retinopathy. However, the mechanism for the protective effects of PEDF against diabetic retinopathy (DR) is presently unclear. As inflammation plays a role in DR, the present study determined the effect of PEDF on inflammation. Western blot analysis and ELISA demonstrated that retinal and plasma PEDF levels were drastically decreased in rats with endotoxin-induced uveitis (EIU), which sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
230
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(246 citation statements)
references
References 56 publications
(86 reference statements)
14
230
0
2
Order By: Relevance
“…PEDF, which has anti-oxidant, anti-inflammatory and anti-angiogenic effects, has been closely associated with diabetic vascular disease, particularly retinopathy [13,14]. Plasma PEDF levels are increased in metabolic syndrome [18] and in type 1 and type 2 diabetes in the presence of complications [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEDF, which has anti-oxidant, anti-inflammatory and anti-angiogenic effects, has been closely associated with diabetic vascular disease, particularly retinopathy [13,14]. Plasma PEDF levels are increased in metabolic syndrome [18] and in type 1 and type 2 diabetes in the presence of complications [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in non-diabetic women indicated that rising serum endoglin and sFlt1/PlGF ratio herald the onset of pre-eclampsia [7]. Pigment epithelium-derived factor (PEDF), a novel anti-angiogenic protein, is also altered in diabetes and its increased serum levels are associated with diabetic vascular complications [13,14]. Although it is unclear whether PEDF is released from placental tissues in pre-eclampsia, PEDF could be implicated as a maternal risk factor in the pathogenesis of pre-eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials in patients with diabetic macular edema have shown beneficial effects of anti-VEGF agents in reducing retinal vascular permeability as assessed by fluorescein angiography and decreasing macular edema as shown by optical coherence tomography (Avery et al, 2006;Haritoglou et al, 2006;Jorge et al, 2006;Starita et al, 2007). Recent data indicate that intravitreal injections of PEDF can also reduce vascular hyper-permeability in diabetic rats by a process associated with decreased levels of a variety of inflammatory mediators, including VEGF, VEGFR-2, MCP-1, TNF-α and ICAM-1 (Zhang et al, 2006a(Zhang et al, , 2006b). Studies of the mechanisms by which VEGF induces the vascular permeability increase indicate that multiple pathways are involved.…”
Section: Vegf and Vascularmentioning
confidence: 99%
“…In recent years, accumulating evidence suggests that inflammation is a key event in the pathogenesis of diabetic vascular complications (Abu El-Asrar et al 1997, Mitamura et al 2001, Hernández et al 2005. In early stages of diabetic retinopathy, expression of pro-inflammatory cytokines, adhesion molecules, and chemokines is significantly up-regulated in the retina, in parallel with breakdown of blood-retina barrier and increased vascular permeability (Joussen et al 2004, Zhang et al 2006. Moreover, enhanced chemokine secretion into the retina and vitreous triggers recruitment and accumulation of monocyte/macrophage from blood to retina, contributing significantly to endothelial cell damage, capillary occlusion, non-perfusion, and neovascularization in the retina in diabetic retinopathy (Schröder et al 1991, Tashimo et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In diabetic retinopathy, MCP-1 levels in the vitreous are significantly elevated in patients with proliferative diabetic retinopathy (Abu El-Asrar et al 1997, Mitamura et al 2001, Hernández et al 2005. In streptozotocin (STZ)-induced diabetic animals, expression of MCP-1 is also up-regulated in the retina and correlates with increased retinal vascular permeability (Zhang et al 2006). In oxygen-induced ischemic retinopathy, a commonly accepted model for proliferative diabetic retinopathy, mRNA and protein levels of MCP-1 are increased in hypoxic inner retina at 3 and 12 h respectively after ischemia (Yoshida et al 2003).…”
Section: Introductionmentioning
confidence: 99%